Upregulated FADD is associated with poor prognosis, immune exhaustion, tumor malignancy, and immunotherapy resistance in patients with lung adenocarcinoma - He, Miao; He, Yingying; Xu, Jian; Zhang, Youcai; Cao, Xiaoyu; Wang, Li; Luo, Feng (Frontiers in Oncology, 2023)
Background: FAS-associated death structural domain (FADD) proteins are important proteins that regulate apoptosis and are also involved in many nonapoptotic pathways in tumors. However, how dysregulated FADD affects the development of lung adenocarcinoma (LUAD) remains unknown.Transcriptome profiles and corresponding clinical information of LUAD patients were convened from different databases, and the results were validated by qRT-PCR and cell counting kit-8 using LUAD cell lines. Potential associations between FADD and tumor malignancy, the immune microenvironment, genomic stability, and treatment sensitivity in LUAD patients were revealed by systematic bioinformatics analysis.Results: FADD was significantly overexpressed in LUAD, and patients with higher expression levels of FADD had a worse prognosis and more advanced tumor stage. Functional analysis revealed that elevated expression of FADD was associated with cell cycle dysregulation, angiogenesis, and metabolic disturbances. In addition, overexpression of FADD was associated with a higher infiltration of suppressive immune cells. From a single-cell perspective, cells with lower FADD expression are more active in immune-related pathways. FADD was associated with more genomic mutations, especially TP53. Patients with high FADD expression are more likely to benefit from conventional chemotherapy, while those with low FADD expression are more suitable for immunotherapy.Conclusions: Upregulated FADD is associated with worse prognosis, immune exhaustion, and tumor malignancy in LUAD patients. In addition, FADD can be an efficient indicator for assessing sensitivity to chemotherapy and immunotherapy. Therefore, FADD has the potential to serve as a new target for precision medicine and targeted therapy for LUAD.